Social media supports tourism development in the COVID-19 normal era in Bandung - Wahyuni, Herpita; Purnomo, Eko Priyo; Fathani, Aqil Teguh (Faculty of Communications Science, Dr. Soetomo University, 2021)
This research focuses on social media. We were using Social Media in Supporting Tourism Development During Covid-19: Case Study a New Era Policy in Bandung. This study uses descriptive qualitative research methods with data sources through the Twitter account of the Bandung City Culture and Tourism Office @DisbudparBdg assisted by the NVivo 12 Plus software. We are utilising Social Media to Support Tourism Development During Covid-19: A Case Study of New Era Policy in Bandung by measuring the use of social media in tourism planning, creation, integration, and marketing strategy. This research shows tourism planning in a new standard era by directing outdoor tourism and implementing health protocols. The Tourism Promotion Board integrates cooperation between the Bandung City Culture and Tourism Office and PT Kereta Api Pariwisata. Tourism marketing by providing tourist information can give tourists confidence that Bandung is an attractive and robust destination city in improving health regulations and strictly following health protocol rules during recreation.